A light-transmitting stone composite board and manufacturing method thereof
By wrap the transparent glue around the transparent and bottom surface and the bottom surface, and inject transparent rubber materials at the top to form a three -layer translucent stone composite plate, it solves the existing transparent stone composite plate due to thermal expansion and contraction and force. The deformation or rupture problem caused by unevenness realizes the stability and durability of the composite board.
Patent Information
- Application Number
- CN202010542708.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-06-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-06-15
AI Technical Summary
The existing light-transmissive stone composite panels have a large gap in the thermal expansion and contraction coefficients between stone and glass, which leads to deformation or cracking of the stone, and the outer side of the light-transmissive stone is unevenly subjected to stress, which is prone to deformation or cracking.
Adopt a method of making a transmitting stone composite plate. First, the initial transparent slate and the bottom surface of the top surface are completely wrapped in transparent rubber materials, and then horizontally cut into a semi -wrapped transparent light slate. Three -layer -based transmittance stone composite board.
Through the wrap and injection of transparent glue, uniformly distributed force to avoid translucent slate deformation or rupture, and ensure that the composite board does not deform or damage during processing, transportation, installation and after -sales service.
Smart Images

Figure CN111719799B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite stone materials, in particular to a light-transmitting stone composite board and a manufacturing method thereof. Background Art
[0002] Natural translucent marble, granite and other materials are commonly used as decorative materials and are widely used in building decoration. However, due to their non-renewable nature, large-scale mining has seriously damaged natural resources.
[0003] The utility model patent with the authorization announcement number CN201276804Y and the patent name is a light-transmitting composite stone plate, which is composed of a layer of light-transmitting stone and a layer of glass, and the two layers are composited together by a film. The composite stone plate can not only reduce the use of natural stone, but also achieve the effect of light transmission. However, due to the large difference in the thermal expansion and contraction coefficients of stone and glass, after a long time, the stone will be severely deformed, and even cracks will appear, damaging the surface of the stone. Alternatively, the existing light-transmitting stone composite board uses one of the outer sides of the light-transmitting stone to bond with a glass fiber board or a light-transmitting plastic honeycomb board to form a composite board, and the other outer side of the light-transmitting stone is exposed to the outside, which will also cause the two outer sides of the light-transmitting stone to deform or crack due to uneven force.
[0004] It is necessary to improve the structure and manufacturing process of the existing light-transmitting stone composite panels. Summary of the invention
[0005] The present invention provides a light-transmitting stone composite board and a manufacturing method thereof, which overcomes the shortcomings of the background technology. One of the technical solutions adopted by the present invention to solve the technical problem is:
[0006] A method for manufacturing a light-transmitting stone composite board, comprising:
[0007] Step 10, cutting the light-transmitting stone into initial light-transmitting stone panels, the thickness of the initial light-transmitting stone panels being more than twice the thickness of the light-transmitting stone panels in the finished product of the light-transmitting stone composite panels;
[0008] Step 20, placing the initial light-transmitting stone plate in a non-stick container, and injecting transparent adhesive material into the non-stick container until the top, bottom and surrounding of the initial light-transmitting stone plate are all covered with the transparent adhesive material;
[0009] Step 30, after the transparent adhesive material is solidified, the initial light-transmitting stone plate wrapped with the transparent adhesive material is taken out from the non-adhesive container, and the initial light-transmitting stone plate wrapped with the transparent adhesive material is transversely cut into two semi-wrapped light-transmitting stone plates of substantially the same thickness, wherein the top surface of the semi-wrapped light-transmitting stone plate is not wrapped with the transparent adhesive material, and the bottom surface and the surrounding area are all wrapped with the transparent adhesive material;
[0010] Step 40, setting the thickness of the semi-wrapped light-transmitting stone slab to the thickness of the light-transmitting stone slab in the finished light-transmitting stone composite board;
[0011] Step 50, injecting transparent adhesive material into the top of the semi-wrapped translucent stone slab after the thickness is determined, and after the transparent adhesive material is solidified, a semi-finished product of the translucent stone composite board is formed, and the periphery and the top and bottom surfaces of the semi-finished product are all wrapped with transparent adhesive material;
[0012] Step 60, the transparent adhesive material around the semi-finished light-transmitting stone composite board is removed to form a finished light-transmitting stone composite board with the top and bottom surfaces both being composited with the transparent adhesive material.
[0013] In a preferred embodiment: in step 30 and step 50, the transparent adhesive material used is transparent crystal adhesive, AB adhesive or epoxy resin adhesive.
[0014] In a preferred embodiment: in step 20, the thickness of the transparent adhesive material on the top and bottom surfaces of the initial translucent stone slab is 1-3 mm; in step 50, the thickness of the transparent adhesive material on the top surface of the semi-finished translucent stone composite board is 1-3 mm; in step 60, the thickness of the translucent stone slab in the finished translucent stone composite board is 3-8 mm.
[0015] In a preferred embodiment: in step 60, the thickness of the transparent adhesive material on the top surface of the finished product of the light-transmitting stone composite board is the same as the thickness of the transparent adhesive material on the bottom surface.
[0016] In a preferred embodiment: In step 20, the non-stick adhesive container includes a container body with an opening at the top and a container cover, the inner bottom surface of the container body is provided with a plurality of supporting parts, the initial light-transmitting stone plate is placed on the supporting parts of the container body and there are gaps between the initial light-transmitting stone plate and the inner peripheral wall of the container body, and between the top and bottom surfaces of the initial light-transmitting stone plate and the top opening and the inner bottom surface of the container body respectively, the container cover is provided with a glue injection port, the container cover is placed on the container body, and transparent glue is injected into the container body from the glue injection port to fill the gap between the initial light-transmitting stone plate and the container body.
[0017] In a preferred embodiment: in step 20, before placing the initial light-transmitting stone slab in the non-stick container, a layer of highly light-transmitting glass fiber mesh is bonded to the bottom surface of the initial light-transmitting stone slab.
[0018] In a preferred embodiment: in step 40, the thickness of the light-transmitting stone board in the semi-wrapped light-transmitting stone board and the height of the transparent adhesive material around the light-transmitting stone board are simultaneously set as the thickness of the light-transmitting stone board in the finished light-transmitting stone composite board.
[0019] In a preferred embodiment: in step 10, the initial light-transmitting stone slab is cut from natural stone or spliced from leftover stone materials.
[0020] The second technical solution adopted by the present invention to solve its technical problem is:
[0021] A light-transmitting stone composite board is made by any of the above-mentioned methods for making light-transmitting stone composite boards, comprising a light-transmitting stone board, a first transparent adhesive layer and a third transparent adhesive layer, wherein the first transparent adhesive layer and the third transparent adhesive layer are respectively bonded to the bottom surface and the top surface of the light-transmitting stone board.
[0022] In a preferred embodiment, the thickness of the first transparent adhesive layer is the same as the thickness of the third transparent adhesive layer.
[0023] Compared with the background technology, this technical solution has the following advantages:
[0024] 1. The production method is suitable for the production of ultra-thin and ultra-large light-transmitting stone composite panels. First, the initial light-transmitting panel is completely wrapped with transparent adhesive around the periphery and the top and bottom surfaces, and then it is horizontally cut into two halves. Due to the wrapping of the transparent adhesive, the initial light-transmitting panel can be protected, and the ultra-thin and ultra-large light-transmitting stone panel can be prevented from being directly cut to cause the stone panel to be broken or damaged; and, the transparent adhesive is injected into the top of the semi-wrapped light-transmitting stone panel after cutting to form a semi-finished product of the light-transmitting stone composite panel. At this time, the semi-finished product is wrapped with transparent adhesive around the periphery and the top and bottom surfaces. Finally, the transparent adhesive around the semi-finished product is cut and removed to form a finished product of the light-transmitting stone composite panel with a three-layer structure. Since the top and bottom surfaces of the light-transmitting stone panel of the finished product are both composited with transparent adhesive, the two layers of transparent adhesive have the same force on the light-transmitting stone panel and can offset each other, which can avoid deformation or even serious damage during the processing, transportation, installation and after-sales service of the ultra-large and ultra-thin light-transmitting stone panel.
[0025] 2. The thickness of the translucent stone slab in the finished product of the translucent stone composite board is 3-8 mm, and the thickness of the transparent adhesive material on the top and bottom surfaces of the finished product is 1-3 mm, which can further ensure that the translucent stone slab in the finished product will not deform or crack.
[0026] 3. The thickness of the transparent adhesive material on the top surface of the finished product of the translucent stone composite board is the same as the thickness of the transparent adhesive material on the bottom surface, so that the forces acting on the top and bottom surfaces of the translucent stone board in the finished product are exactly the same and can offset each other.
[0027] 4. Before placing the initial light-transmitting stone slab in the non-stick container, a layer of strong light-transmitting glass fiber mesh is bonded to the bottom surface of the initial light-transmitting stone slab, which can further ensure the strength of the initial light-transmitting stone slab and ensure the smooth transverse cutting of the initial light-transmitting stone slab in step 30. At the same time, the glass fiber mesh is not easy to expand and contract due to heat and cold, and will not affect the force applied to the initial light-transmitting stone slab. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0029] Figure 1 A schematic diagram of the structure of the initial light-transmitting stone slab is shown.
[0030] Figure 2 A schematic diagram of the assembly of the non-stick container and the initial light-transmitting stone plate is shown.
[0031] Figure 3 A cross-sectional view is shown when a non-stick adhesive container is filled with transparent adhesive material.
[0032] Figure 4 The schematic diagram shows a state where an initial light-transmitting stone plate wrapped with transparent adhesive is cut transversely into two half-wrapped light-transmitting stone plates of substantially the same thickness.
[0033] Figure 5 A schematic diagram of the assembly and decomposition of a semi-wrapped translucent stone panel and a glue injection mold is shown.
[0034] Figure 6 The schematic diagram of the assembly of the semi-wrapped translucent stone slab and the injection mold is drawn.
[0035] Figure 7 A schematic diagram is drawn showing the state where the top surface of a semi-wrapped translucent stone slab is filled with transparent adhesive material.
[0036] Figure 8 A cross-sectional schematic diagram of a semi-finished product of a light-transmitting stone composite panel is depicted.
[0037] Fig. 9 A cross-sectional schematic diagram of a finished product of a light-transmitting stone composite panel is depicted. DETAILED DESCRIPTION
[0038] In the claims, description and the above-mentioned drawings of the present invention, unless otherwise clearly defined, the use of terms such as "first", "second" or "third" etc. are for distinguishing different objects rather than for describing a specific order.
[0039] In the claims, specification and the above-mentioned drawings of the present invention, unless otherwise explicitly defined, directional words, such as the terms "center", "lateral", "longitudinal", "horizontal", "vertical", "top", "bottom", "inside", "outside", "up", "down", "front", "back", "left", "right", "clockwise", "counterclockwise", etc., indicating directions or positional relationships are based on the directions and positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction or be constructed and operated in a specific direction, and therefore cannot be understood as limiting the specific protection scope of the present invention.
[0040] In the claims, specification and the above drawings of the present invention, unless otherwise clearly defined, the terms "fixed connection" and "fixed connection" should be understood in a broad sense, that is, any connection method without any displacement relationship and relative rotation relationship between the two parties, that is to say, including non-detachable fixed connection, detachable fixed connection, integral connection and fixed connection through other devices or elements.
[0041] In the claims, description and drawings of the present invention, if the terms "include", "have" and their variations are used, they are intended to mean "including but not limited to".
[0042] Please refer to Figures 1 to 9 A preferred embodiment of a method for manufacturing a light-transmitting stone composite board, the method for manufacturing a light-transmitting stone composite board comprises:
[0043] Step 10, cutting the light-transmitting stone into initial light-transmitting stone panels 10, wherein the thickness of the initial light-transmitting stone panels 10 is twice or more than twice the thickness of the light-transmitting stone panels in the finished product of the light-transmitting stone composite panels;
[0044] In this embodiment, in step 10, the initial light-transmitting stone slab 10 can be cut from natural stone or spliced from stone leftovers. The splicing method can be, for example, splicing multiple stone strips into a striped initial light-transmitting stone slab, or the striped initial light-transmitting stone slab can be cut again to form strips with multiple colors, and then several strips can be spliced again to form a mosaic-like initial light-transmitting stone slab. The specific splicing method is not limited to this.
[0045] Specifically, the size of the initial light-transmitting stone plate 10 is taken as 2410 mm*1210 mm*15 mm as an example, but it is not limited to this size.
[0046] Step 20, placing the initial light-transmitting stone plate 10 in a non-stick container, and injecting transparent adhesive material into the non-stick container until the top and bottom surfaces and the surrounding of the initial light-transmitting stone plate 10 are all covered with transparent adhesive material; for the convenience of explanation, as shown in FIG. Figure 3 As shown, the transparent adhesive material on the top surface of the initial light-transmitting stone plate 10 is defined as a first transparent adhesive material layer 11, the transparent adhesive material on the bottom surface of the initial light-transmitting stone plate 10 is defined as a second transparent adhesive material layer 12, and the transparent adhesive material around the initial light-transmitting stone plate 10 is defined as a surrounding transparent adhesive material layer 13. In this embodiment, in step 20, the transparent adhesive material used is transparent crystal glue, or other transparent adhesive materials such as AB glue or epoxy resin glue can also be used.
[0047] In this embodiment, in step 20, the thickness of the transparent adhesive material on the top and bottom surfaces of the initial light-transmitting stone plate 10 is 1-3 mm, that is, the thickness of the first transparent adhesive layer 11 and the thickness of the second transparent adhesive layer 12 are 1-3 mm; because the surrounding transparent adhesive layer 13 needs to be cut off in the end, the thickness of the surrounding transparent adhesive layer 13 can be set arbitrarily. Among them, the thickness of the first transparent adhesive layer 11 and the thickness of the second transparent adhesive layer 12 are preferably the same, and the optimal thickness of the two is 2 mm. The thickness of the first transparent adhesive layer 11 and the thickness of the second transparent adhesive layer 12 can also be adjusted according to the size of the actual finished product to ensure sufficient support strength. In this embodiment, the thickness of the first transparent adhesive layer 11 and the thickness of the second transparent adhesive layer 12 are both 2 mm.
[0048] like Figure 2 As shown, the non-stick adhesive container includes a container body 20 with an opening at the top and a container cover 21. The inner bottom surface of the container body 20 is provided with a plurality of support portions 22. The initial light-transmitting stone plate 10 is placed on the support portions 22 of the container body 20, and there are gaps between the initial light-transmitting stone plate 10 and the inner peripheral wall of the container body 20, and between the top and bottom surfaces of the initial light-transmitting stone plate 10 and the top opening and the inner bottom surface of the container body 20, respectively. The container cover 21 is provided with a glue injection port 23. The container cover 21 is placed on the container body 20, and transparent glue is injected into the container body 20 from the glue injection port 23 to fill the gap between the initial light-transmitting stone plate 10 and the container body 20. Among them, the support portion 22 adopts a cylindrical structure. The transparent glue material injected from the glue injection port 23 flows through the gap between the initial light-transmitting stone plate 10 and the inner peripheral wall of the container body 20, and then enters the gap between the bottom surface of the initial light-transmitting stone plate 10 and the inner bottom surface of the container body 20, so as to fill the gap between the bottom surface of the initial light-transmitting stone plate 10 and the inner bottom surface of the container body 20, the gap between the initial light-transmitting stone plate 10 and the inner peripheral wall of the container body 20, and the gap between the top surface of the initial light-transmitting stone plate 10 and the top opening of the container body 20 with the transparent glue material. The non-stick container can be made of silicone material, or other non-stick materials, but is not limited thereto.
[0049] In this embodiment, in step 20, before placing the initial light-transmitting stone slab 10 in the non-stick container, a layer of highly light-transmitting glass fiber mesh (not shown in the figure) is bonded to the bottom surface of the initial light-transmitting stone slab 10. The highly light-transmitting glass fiber mesh can support the initial light-transmitting stone slab 10 during the cutting process in step 30.
[0050] Step 30, such as Figure 4As shown, after the transparent adhesive material is cured, the initial light-transmitting stone plate 10 wrapped with the transparent adhesive material is taken out from the non-adhesive container, and the initial light-transmitting stone plate 10 wrapped with the transparent adhesive material is cut horizontally into two semi-wrapped light-transmitting stone plates 30 of substantially the same thickness, wherein the top surface of the semi-wrapped light-transmitting stone plate 30 is not wrapped with the transparent adhesive material, and the bottom surface and the surroundings are all wrapped with the transparent adhesive material; at this time, the thickness of the light-transmitting stone plate 31 in the semi-wrapped light-transmitting stone plate 30 is approximately 5-6 mm, and one of the semi-wrapped light-transmitting stone plates 30 is taken for subsequent production, and the production process of the other semi-wrapped light-transmitting stone plate 30 is the same.
[0051] Step 40, the semi-wrapped light-transmitting stone slab 30 is thickness-set, and the thickness of the light-transmitting stone slab 31 of the semi-wrapped light-transmitting stone slab 30 is set to the thickness of the light-transmitting stone slab 62 in the finished product 70 of the light-transmitting stone composite board; the thickness of the light-transmitting stone slab 62 in the finished product 70 of the light-transmitting stone composite board is 3-8 mm, that is, the thickness of the light-transmitting stone slab 41 of the semi-wrapped light-transmitting stone slab 40 after thickness-setting is 3-8 mm; in this embodiment, the thickness of the light-transmitting stone slab 62 in the finished product 70 of the light-transmitting stone composite board is 3.5 mm. In order to facilitate the thickness setting operation, in step 40, the thickness of the light-transmitting stone slab 31 in the semi-wrapped light-transmitting stone slab 30 and the height of the transparent adhesive layer 13 surrounding the light-transmitting stone slab are simultaneously set to the thickness of the light-transmitting stone slab 62 in the finished product 70 of the light-transmitting stone composite board, so that the top of the semi-wrapped light-transmitting stone slab 30 is a flat surface, such as Figure 5 shown.
[0052] Step 50, injecting transparent adhesive material into the top of the semi-wrapped translucent stone slab 40 after the thickness is determined, and after the transparent adhesive material is cured, a semi-finished product 60 of the translucent stone composite board is formed, and the periphery and the top and bottom surfaces of the semi-finished product 40 are all wrapped with transparent adhesive material; Figure 5 and Figure 6 As shown, a hollow glue injection mold 50 is used, and the glue injection mold 50 is placed around the semi-wrapped light-transmitting stone plate 40 with a set thickness. At this time, the semi-wrapped light-transmitting stone plate 40 with a set thickness is in contact with the inner wall surface of the glue injection mold 50 to prevent the transparent glue from flowing out of the gap between the two. Then, as shown in FIG. Figure 7 As shown, a transparent adhesive is injected into the semi-wrapped transparent stone plate 40 after the thickness is determined; then, after the transparent adhesive is solidified, the adhesive injection mold 50 is demoulded; Figure 8As shown, a semi-finished product 60 of a light-transmitting stone composite panel is formed. The distance between the top surface of the semi-wrapped light-transmitting stone slab 40 after the thickness is determined and the top surface of the glue injection mold 50 is the thickness required for glue injection. In this embodiment, the thickness required for glue injection is 2 mm, but it is not limited thereto, and can be selected between 1-3 mm. For ease of explanation, the transparent glue material on the top surface of the semi-wrapped light-transmitting stone slab 40 after the thickness is determined is defined as a third transparent glue material layer 61. In this embodiment, in step 50, the transparent glue material used is transparent crystal glue, or other transparent glue materials such as AB glue or epoxy resin glue can also be used. The glue injection mold can be made of silicone material, or other non-adhesive materials, but is not limited thereto.
[0053] Step 60, the transparent adhesive material around the semi-finished product 60 of the light-transmitting stone composite board is cut off to form a finished product 70 of the light-transmitting stone composite board whose top and bottom surfaces are both composited with transparent adhesive material, that is, the finished product 70 is composited by the third transparent adhesive layer 61, the light-transmitting stone board 62, and the first transparent adhesive layer 11, or the finished product 70 is composited by the third transparent adhesive layer 61, the light-transmitting stone board 62 and the second transparent adhesive layer 12.
[0054] In this embodiment, in step 60, the thickness of the light-transmitting stone board 62 in the finished product 70 of the light-transmitting stone composite board is 3-8 mm. Moreover, the thickness of the transparent adhesive material on the top surface of the finished product 70 of the light-transmitting stone composite board is the same as the thickness of the transparent adhesive material on the bottom surface. Fig. 9 As shown, in the finished product 70 of the light-transmitting stone composite board, the size of the light-transmitting stone board 62 is 1200 mm*2400 mm*3.5 mm, and the size of the third transparent adhesive layer 61 and the first transparent adhesive layer 11 are both 1200 mm*2400 mm*2 mm.
[0055] Please refer to Fig. 9 , is a preferred embodiment of a translucent stone composite board, which is made by the above-mentioned method for making a translucent stone composite board, and includes a translucent stone board 62, a first transparent adhesive layer 11 and a third transparent adhesive layer 61, and the first transparent adhesive layer 11 and the third transparent adhesive layer 61 are respectively bonded to the bottom surface and the top surface of the translucent stone board 62.
[0056] In this embodiment, the thickness of the first transparent adhesive layer 11 is the same as the thickness of the third transparent adhesive layer 61 .
[0057] In this embodiment, the thickness of the light-transmitting stone plate 62 in the composite plate is 3-8 mm, and the thickness of the first transparent adhesive layer 11 and the thickness of the third transparent adhesive layer 61 are both 1-3 mm.
[0058] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A method for manufacturing a light-transmitting stone composite panel, characterized in that: It includes: Step 10, cutting the light-transmitting stone into initial light-transmitting stone panels, the thickness of the initial light-transmitting stone panels being more than twice the thickness of the light-transmitting stone panels in the finished product of the light-transmitting stone composite panels; Step 20, placing the initial light-transmitting stone plate in a non-stick container, and injecting transparent adhesive material into the non-stick container until the top, bottom and surrounding of the initial light-transmitting stone plate are all covered with the transparent adhesive material; Step 30, after the transparent adhesive material is solidified, the initial light-transmitting stone plate wrapped with the transparent adhesive material is taken out from the non-adhesive container, and the initial light-transmitting stone plate wrapped with the transparent adhesive material is transversely cut into two semi-wrapped light-transmitting stone plates of substantially the same thickness, wherein the top surface of the semi-wrapped light-transmitting stone plate is not wrapped with the transparent adhesive material, and the bottom surface and the surrounding area are all wrapped with the transparent adhesive material; Step 40, setting the thickness of the semi-wrapped light-transmitting stone slab to the thickness of the light-transmitting stone slab in the finished light-transmitting stone composite board; Step 50, injecting transparent adhesive material into the top of the semi-wrapped translucent stone slab after the thickness is determined, and after the transparent adhesive material is solidified, a semi-finished product of the translucent stone composite board is formed, and the periphery and the top and bottom surfaces of the semi-finished product are all wrapped with transparent adhesive material; Step 60, the transparent adhesive material around the semi-finished light-transmitting stone composite board is removed to form a finished light-transmitting stone composite board with the top and bottom surfaces both being composited with the transparent adhesive material.
2. The method for manufacturing a light-transmitting stone composite board according to claim 1, characterized in that: In step 30 and step 50, the transparent adhesive material used is AB adhesive.
3. The method for manufacturing a light-transmitting stone composite board according to claim 1, characterized in that: In step 20, the thickness of the transparent adhesive material on the top and bottom surfaces of the initial translucent stone slab is 1-3 mm; in step 50, the thickness of the transparent adhesive material on the top surface of the semi-finished translucent stone composite board is 1-3 mm; in step 60, the thickness of the translucent stone slab in the finished translucent stone composite board is 3-8 mm.
4. The method for manufacturing a light-transmitting stone composite board according to claim 3, characterized in that: In step 60, the thickness of the transparent adhesive material on the top surface of the finished product of the light-transmitting stone composite board is the same as the thickness of the transparent adhesive material on the bottom surface.
5. The method for manufacturing a light-transmitting stone composite board according to claim 3, characterized in that: In step 20, the non-stick adhesive container includes a container body with an opening at the top and a container cover, the inner bottom surface of the container body is provided with a plurality of supporting parts, the initial light-transmitting stone plate is placed on the supporting parts of the container body, and there are gaps between the initial light-transmitting stone plate and the inner peripheral wall of the container body, and between the top and bottom surfaces of the initial light-transmitting stone plate and the top opening and the inner bottom surface of the container body respectively, the container cover is provided with a glue injection port, the container cover is placed on the container body, and transparent glue is injected into the container body from the glue injection port to fill the gap between the initial light-transmitting stone plate and the container body.
6. The method for manufacturing a light-transmitting stone composite board according to claim 5, characterized in that: In step 20, before placing the initial light-transmitting stone slab in the non-stick container, a layer of highly light-transmitting glass fiber mesh is bonded to the bottom surface of the initial light-transmitting stone slab.
7. The method for manufacturing a light-transmitting stone composite board according to claim 1, characterized in that: In step 40, the thickness of the light-transmitting stone panels in the semi-wrapped light-transmitting stone panels and the height of the transparent adhesive material surrounding the light-transmitting stone panels are simultaneously set as the thickness of the light-transmitting stone panels in the finished light-transmitting stone composite panel.
8. The method for manufacturing a light-transmitting stone composite board according to claim 1, characterized in that: In step 10, the initial light-transmitting stone slab is cut from natural stone or spliced from leftover stone.
Citation Information
Patent Citations
Transparent composite stone sheet material
CN201276804Y
Method for producing cementation healing fussure stone
CN102320861A
Composite board made of natural stone
CN202706410U
Light-transmitting stone composite board
CN212478364U
Stone panel fitted with glass and the manufacturing method
KR1020030044723A